2018
DOI: 10.1542/peds.2018-0767
|View full text |Cite
|
Sign up to set email alerts
|

Human and Bovine Colostrum for Prevention of Necrotizing Enterocolitis: A Meta-analysis

Abstract: Bovine or human colostrum has no effect on severe NEC, mortality, culture-proven sepsis, feed intolerance, or length of stay. Additional research focused on the impact on enteral feeding may be needed to confirm the findings on this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
11
0
4
Order By: Relevance
“…Although our review focusing on the effects of OAC on the incidence of NEC, LOS, and death showed negative outcomes, there are still some evidences concerning the effects of OAC as a beneficial trial for preterm infants. Achieving full enteral feeding is an important health outcome since it is related to the removal of the central line, possibly, to lower infection rates [52]. The duration of hospital stay reflects the condition of preterm infants and the related medical costs, and the pooled results indicate that OAC would shorten the time to achieve these two goals.…”
Section: Discussionmentioning
confidence: 99%
“…Although our review focusing on the effects of OAC on the incidence of NEC, LOS, and death showed negative outcomes, there are still some evidences concerning the effects of OAC as a beneficial trial for preterm infants. Achieving full enteral feeding is an important health outcome since it is related to the removal of the central line, possibly, to lower infection rates [52]. The duration of hospital stay reflects the condition of preterm infants and the related medical costs, and the pooled results indicate that OAC would shorten the time to achieve these two goals.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto al primero, varios participantes plantean que la evidencia científica es aún insuficiente, lo que refleja la discusión científica internacional. Acorde a ésta, hay estudios que favorecen la praxis de suministro enteral trófico con calostro de la madre de las primeras horas de vida, mientras otros discuten su utilidad o nivel de evidencia para la prevención de morbimortalidad neonatal, y específicamente, de ECN 10,11,14,16,17,[26][27][28][29][30][31][32][33] . Otra razón aducida por algunos participantes es el desconocimiento del conjunto de experiencias desarrolladas en Chile.…”
Section: Discussionunclassified
“…Resultados: El uso de calostro en prematuros se da de modo protocolizado en dos de las tres unidades de alta complejidad neonatal de la región de Valparaíso. Los participantes opinan trófica, aporte inmunológico y prevención de enfermedades gastrointestinales 6,9 ; además de tiempo para lograr alimentación enteral completa y favorecer la lactancia materna 10,11 . Diversas revisiones e investigaciones han indagado en el riesgo y beneficio profiláctico de suministro temprano de calostro materno desde las primeras horas de vida, aún en prematuros extremos [9][10][11][12][13][14] .…”
Section: Introductionunclassified
See 2 more Smart Citations